Organ Donation in the Context of Brain Death in Muslim Countries: Bioethical Positions - Mohammed, Alqahtani Ibtesam (International Journal of Innovative Research in Medical Science, 2020)
One of the miracles of modern medicine for patients with end stage organ failure is organ transplantation. The Organ Procurement and Transplantation Network (OPTN) defines organ donation as giving an organ, tissue, cells, or part of an organ from a living or deceased person (i.e., the donor) to a living person in need (i.e., the recipient). In the last two decades, the number of organ transplants has gradually increased; however, the demand for organ transplantation exceeds the number of available donors. Organs from brain dead donors have been suggested as an alternative option for increasing donation rates when living donors are not available. This article explores the debate surrounding brain death organ donation in Muslim countries. Because organ transplantation is based on Ijtihad, Muslim jurists have no clear-cut text in the Holy Quran or Sunna to use as a foundation for judgment. This has made organ transplants an issue among Muslim scholars and researchers, splitting them into two opinion groups, with one side seeing organ transplantation as legal and the other believing it to be illegal. However, all individuals have the right to choose whether they want to help others by sacrificing parts of themselves and donating their organs. Autonomy, justice, and beneficence must be employed in organ transplantation decision-making.